Heterosis for yield and yield components in rice (Oryza sativa L.) - Vanaja, T.; Babu, Luckins C. (Journal of Tropical Agriculture, 2006)
Eight genetically diverse high yielding rice cultivars selected from clusters formulated through Mahalanobis D2 statistics were crossed in a diallel fashion. The parents and crosses were evaluated and heterosis for yield and its principal components estimated. Results suggest that yield increase was largely due to significant and favourable heterosis in yield components viz., number of spikelets panicle–1, panicle length, leaf area plant-1 (at maximum tillering stage) and number of panicles m-2. Five top heterotic crosses over their mid and better parents for each trait were identified.